Food avoidance strategies in eosinophilic oesophagitis. Issue 3 (27th February 2019) - Cianferoni, Antonella; Shuker, Michelle; Brown‐Whitehorn, Terri; Hunter, Hannah; Venter, Carina; Spergel, Jonathan M.
Summary: Eosinophilic oesophagitis (EoE) is a chronic disease associated with significant morbidity that can result in permanent fibrosis and stricture formation. Given the complexity, a multidisciplinary approach is recommended to manage these patients. In the majority of children with EoE not responsive to proton‐pump inhibitor (PPI), inflammation is driven by sensitivity to foods and treatment with an elimination diet can be effective. Foods most commonly identified to trigger EoE in children are milk and wheat, but egg, soy, meats and grains can also be triggers. Foods can be eliminated using a step‐down or step‐up approach. If the goal is to achieve quick remission, elemental diet or six food elimination diets are the most effective. A step‐up approach starting from a 1‐2 food elimination diet and increasing the number of foods based on a personalized dietary approach is recommended if the goal is to achieve remission using the least number of endoscopies and with increased acceptability to the patient. Children with EoE on elimination diets require frequent monitoring of growth and nutrition, as well as screening for symptoms of EoE, allergy and mindfulness regarding psychosocial impact of chronic disease on the family and child. Current research focused on tools to select patients who mostly will benefit from dietary treatment, identify relevant food allergens, obtain oesophageal tissue non‐invasively and induce tolerance will greatly improve the treatment of EoE.